2020
DOI: 10.1039/d0cc03099f
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh rate capability and long cycling stability of dual-ion batteries enabled by TiO2 microspheres with abundant oxygen vacancies

Abstract: By introducing oxygen vacancies, TiO2 microspheres exhibit outstanding electrochemical performance for dual Mg/Li-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…An additional component is deconvoluted at 463.87 eV for CN–TiO 2 and 463.66 eV for CNOv–TiO 2 , ascribed to Ti 3+ . The bathochromic shift phenomenon of O 1s and Ti 2p spectra confirmed together the successful introduction of Ti–C bond and OVs . Quantitative analysis showed that the atomic ratios of Ti and O in CN–TiO 2 and CNOv–TiO 2 samples were 23.25 and 46.07 at % and 26.76 and 51.59 at %, respectively, which also proved that there are more OVs in the CNOv–TiO 2 sample.…”
Section: Resultsmentioning
confidence: 62%
“…An additional component is deconvoluted at 463.87 eV for CN–TiO 2 and 463.66 eV for CNOv–TiO 2 , ascribed to Ti 3+ . The bathochromic shift phenomenon of O 1s and Ti 2p spectra confirmed together the successful introduction of Ti–C bond and OVs . Quantitative analysis showed that the atomic ratios of Ti and O in CN–TiO 2 and CNOv–TiO 2 samples were 23.25 and 46.07 at % and 26.76 and 51.59 at %, respectively, which also proved that there are more OVs in the CNOv–TiO 2 sample.…”
Section: Resultsmentioning
confidence: 62%
“…Moreover, the cathode in APC-LiTFSI shows a smaller polarization and higher reversibility than those in APC-LiCl at a high rate (Figure S10b and c). Compared with previously reported cathodes in MLHBs (Figure f and Table S1), NiCo 2 S 4 in the APC-LiTFSI electrolyte represents the best rate performance. ,,,,, According to calculation of the integral of U discharge and Q specific capacity , an ultrahigh gravimetric energy density of 708 Wh kg –1 (based on the weights of active materials) is achieved at 0.1 A g –1 with a capacity of 746.1 mAh g –1 . Even when the binder and conductive carbon black are included, the electrode exhibits a high energy density of 566 Wh kg –1 (Figure S11a and b).…”
Section: Resultsmentioning
confidence: 81%
“…Step 3: 2MgO 2 ↔ 2MgO + O 2 (10) During the charge process, MgO 2 decomposed first, followed by more limited MgO decomposition. The low energy efficiency and the capacity loss could be attributed to the incomplete decomposition of discharge products [Figure 10B].…”
Section: Cathodic Discharge Products Of Rechargeable Mg-air Batteriesmentioning
confidence: 99%
“…Among the various rechargeable multivalent metal-air batteries, Mg-air batteries are considered to be "green" power sources of next-generation battery technologies for electric automobiles and large-scale energy storage due to their high theoretical energy densities (14 kWh•L -1 and 3.9 kWh•kg -1 , based on MgO) [8] . Importantly, Mg has a relatively low redox potential [-2.36 V vs. standard hydrogen electrode (SHE)], low cost ($0.26 g -1 ) [10] , sustainability (2.08% in the Earth's crust) [7,8] , a less reactive nature and resistance to dendrite formation [11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation